Mice lacking major histocompatibility complex class I and class II molecules. - Grusby, M J (1993)
Mice lacking major histocompatibility complex (MHC) antigens were generated by mating beta 2-microglobulin-deficient, and therefore class I-deficient, animals with MHC class II-deficient animals. When housed under sterile conditions, the resulting MHC-deficient mice appear healthy, survive for many months, and breed successfully. Phenotypically, MHC-deficient mice are depleted of CD4+ and CD8+ T cells in peripheral lymphoid organs due to a lack of appropriate restricting elements. In contrast, the B-cell compartment of these animals appears intact, and MHC-deficient mice can mount specific antibody responses when challenged with a T-independent antigen. Spleen cells from MHC-deficient animals are poor stimulators and responders in a mixed lymphocyte reaction. Despite their relatively weak cellular immune responses in vitro, MHC-deficient mice reject allogeneic skin grafts with little delay, and grafts from MHC-deficient animals are rapidly rejected by normal allogeneic recipients. Taken together, these results emphasize the plasticity of the immune system and suggest that MHC-deficient mice may be useful for examining compensatory mechanisms in severely immunocompromised animals.